Examining the Effect of Pileup on the Accuracy of Sharp Indentation Testing - Zhongbin Tang; Yazhou Guo; Zhaohu Jia; Yulong Li; Qiuming Wei (Advances in Materials Science and Engineering)
One essential problem related to instrumented indentation is the effect of pileup, which could introduce significant errors on the measured hardness and elastic modulus. In this work, we have assessed some critical issues associated with instrumented indentation by means of numerical simulation. Dimensional analysis is adopted to acquire the principal governing parameters of the process, such as the ratio of yield strength to elastic modulus (Y/E) and the ratio of indentation depth to maximum penetration depth (h/hmax). The dimensional analysis provides a general understanding on the relationships among these dimensionless variables and their influence on the test results. Three kinds of indenters, that is, conical, Berkovich, and Vickers indenter, are comparatively studied. The dependence of pileup on the dimensionless parameters and its effect on the simulation results are also given. These findings are instructive for measuring the mechanical properties by instrumented indentation, especially when the effect of pileup is involved.